Potensi Pemanfaatan Limbah Industri Sebagai Material Konstruksi Berkelanjutan: Kajian Tailing Bauksit, Red Mud, Fly Ash, dan Bottom Ash - Julyan Purnomo; Firmanilah Kamil (Jurnal Konstruksi dan Infrastruktur : Teknik Sipil dan Perencanaan, 2026)
Ketapang Regency, West Kalimantan, is one of the regions with intensive industrial activity, particularly bauxite mining and coal-fired power plants (CFPPs), which generate large amounts of industrial waste such as bauxite tailings, red mud, fly ash, and bottom ash. To date, most of this waste has not been optimally utilized and has the potential to cause environmental issues. This study aims to conduct basic physical characterization of the four types of waste and assess their potential for utilization in concrete construction for sustainable transportation infrastructure. The methodology employed includes testing for moisture content, particle size distribution, bulk density, specific gravity, water absorption, and clay content. Test results indicate that fly ash exhibits pozzolanic properties, bauxite tailings have potential as an alternative fine aggregate, bottom ash approaches sand gradation though it requires preliminary treatment, while red mud is more suitable for use as a filler or cement substitute in limited quantities after chemical stabilization. These findings indicate that the utilization of industrial waste in Ketapang can serve as a strategic solution in supporting environmentally friendly infrastructure development while reducing dependence on conventional natural resources.